2022
DOI: 10.1021/jacs.2c07473
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Nature and Role of Layered Cation Ordering in Cation-Disordered Rock-Salt Cathodes

Abstract: Cation-disordered rock salts (DRXs), a new class of cathode materials for Li-ion batteries, have attracted a great amount of attention in recent years due to their fascinatingly simple cubic structure, highly diverse composition, and great electrochemical performance. As cations in DRXs are randomly distributed in a long range, how the cations are spatially arranged is an intriguing question for the community of solid-state materials chemistry. In this work, we report the vibrational structure of a series of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
(86 reference statements)
2
20
0
Order By: Relevance
“…Unlike the cracking of layered oxide cathodes, including Li-stoichiometric or Li/Mn-rich oxides, which gradually happens during the long-term cycling, immediate cracking happens in DRXs during their first cycle. Recently, Wang et al suggested that DRX is a set of randomly oriented O3-packing blocks based on layeredlike anisotropy (Wang et al, 2022). Although the study does not include any mechanical insights, the discovery of random anisotropy suggests that DRXs may weaker against the internal stress (Ortiz and Suresh, 1993;Lim et al, 2017).…”
Section: Degradation Of Fluorinated Cationdisordered Rock-saltsmentioning
confidence: 99%
“…Unlike the cracking of layered oxide cathodes, including Li-stoichiometric or Li/Mn-rich oxides, which gradually happens during the long-term cycling, immediate cracking happens in DRXs during their first cycle. Recently, Wang et al suggested that DRX is a set of randomly oriented O3-packing blocks based on layeredlike anisotropy (Wang et al, 2022). Although the study does not include any mechanical insights, the discovery of random anisotropy suggests that DRXs may weaker against the internal stress (Ortiz and Suresh, 1993;Lim et al, 2017).…”
Section: Degradation Of Fluorinated Cationdisordered Rock-saltsmentioning
confidence: 99%
“…For example, Wang et al systematically studied the SRO in a series of Mn-and Fe-based DRX materials and revealed the widespread existence of layered-like domains. 36 The shuffled layer scheme they proposed for the DRX structure model may be beneficial for percolating Li diffusion. In current LTNNO material, the Ni-rich 4-TM clusters and Ti-rich 1-TM clusters are reminiscent of the NiO and Li 2 TiO 3 structure, respectively, implying the formation of NiO-and Li 2 TiO 3 -like domains.…”
Section: Structural Feature Statistics and Sro Existence In Ltnnomentioning
confidence: 99%
“…The rules for SRO formation have not been fully elucidated. The ways of SRO pattern manifestation are various and closely related to the DRX material composition. Some high-valence d 0 cations, like Ti 4+ , Nb 5+ , and Mo 6+ , were found critical in promoting cation mixing and breaking SRO .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of the reduced lithium percolation in disordered rock salt materials relative to the random limit is understood to be a consequence of the short-range ordering preferences of the cations, which are comprised of contributions from bonding preferences and electrostatics [8,25,28,29]. Thus, finding ways to suppress unfavourable short-range ordering is crucial for improving the capacity and overall performance of disordered rock salt cathode materials.…”
Section: Introductionmentioning
confidence: 99%